Scanning Electron Microscopy and Atomic Force Microscopy: Topographic and Dynamical Surface Studies of Blends, Composites, and Hybrid Functional Materials for Sustainable Future - Joanna Rydz; Alena Šišková; Anita Andicsová Eckstein (Advances in Materials Science and Engineering)
Microscopic techniques are often used in material science, enabling the assessment of the morphology, composition, physical properties, and dynamic behaviour of materials. The review focuses on the topographic and dynamical surface studies of (bio)degradable polymers, in particular aliphatic polyesters, the most promising ones. The (bio)degradation process promotes physical and chemical changes in material properties that can be characterised by microscopic techniques. These changes occurring both under controlled conditions as well as in the processing stage or during use indicate morphological and structural transformations resulting from the deterioration of the material and have a significant impact on the characteristic of materials used in many applications, for example, for use as packaging.